MOTIVATIONAL STRATEGIES IN SPEAKING FOR THE 4TH AND 5TH GRADERS IN LOWER MOVER CLASSES AT FOREIGN LANGUAGE CENTER A, HANOI - Tăng, Thị Quỳnh Thơ (2021)
The modern language teaching approach puts a strong emphasis on communicative language teaching and learner-centered activities. Therefore, motivational strategies in speaking have been worldwide applied in English Language Teaching. In teaching English to children in Vietnam, motivational strategies have recently utilized but only in a few learning centers in big cities. In attempts to figure out the motivational strategies applied in speaking lessons, the researcher investigated into the frequency of applying motivational strategies by teachers at center A Hanoi for the 4th and 5th graders in Lower Mover classes and the strategies that motivate learners most as perceived by themselves